Aspects correlates with Scandinavian Stroke Scale for predicting early neurological impairment - Luvizutto, Gustavo José [UNESP]; Gabriel, Maicon Goncalves [UNESP]; Braga, Gabriel Pereira [UNESP]; Fernandes, Thiago Dias [UNESP]; Resende, Luiz Antonio de Lima [UNESP]; Pontes Neto, Octavio Marques; Bazan, Rodrigo [UNESP] (Assoc Arquivos Neuro- Psiquiatria, 2015)
Objective: To investigate the correlation between the Alberta Program Early CT Score (ASPECTS) and the Scandinavian Stroke Scale (SSS) for the evaluation of neurological impairment in patients with acute stroke. Method: 59 patients with a first acute ischemic stroke were evaluated. The ASPECTS were evaluated by 2 neurologists at admission and by another neurologist after 48 hours. The NIHSS and SSS was applied to determinate stroke severity. Correlations and agreements were analysed statistically by Spearman and Kappa tests. Results: ASPECTS was correlated with National Institute of Health Stroke Scale (NIHSS) at admission (r = -0.52; p < 0.001) and SSS (r = 0.50; p < 0.001). The ASPECTS and SSS items were most correlated with arm (r = 0.52; p < 0.001) and hand (r = 0.49; p < 0.001) motor power, and speech (r = 0.51; p < 0.001). The SSS of 25.5 shows sensitivity (68%) and specificity (72%) when associated with ASPECTS <= 7. Conclusion: The SSS can predict worst neurological impairment when associated with lower values of ASPECTS.

Objetivo: Investigar a relação entre o Alberta Program Early CT Score (ASPECTS) e a Scandinavian Stroke Scale (SSS) para avaliação da incapacidade neurológica de pacientes na fase aguda do acidente vascular cerebral (AVC). Método: 59 pacientes com diagnóstico de primeiro AVC foram avaliados. O ASPECTS foi avaliado por 2 neurologistas na admissão e por outro neurologista após 48 horas. O National Institute of Health Stroke Scale (NIHSS) e SSS foram aplicadas para determinar a gravidade do AVC. As correlação e concordâncias foram analisadas estatisticamente pelos testes de Spearman e Kappa. Resultados: ASPECTS foi correlacionado com o NIHSS na admissão (r = -0,52; p < 0,001) e SSS (r = 0,50; p < 0,001). O ASPECTS e os itens do SSS que mais se relacionaram foram força do braço (r = 0,52; p < 0,001), da mão (r = 0,49; p < 0,001) e fala (r = 0,51; p < 0,001). A pontuação da SSS de 25,5 mostrou sensibilidade (68%) e especificidade (72%) quando associado ao ASPECTS ≤ 7. Conclusão: A SSS pode predizer pior incapacidade neurológica quando associado a baixos valores do ASPECTS.
Correlação do ASPECTS com a escala Escandinava de AVC para predizer comprometimento neurológico precoce
Keywords: Stroke; Neuroimaging; Outcome measures; Scales; Acidente vascular cerebral; Neuroimagem; Medidas de desfecho funcional; Escalas